Heparin in the Management of Extensive Burns - J. L. Srivastava; K. Ramesh Babu; V. K. Tewari; R. P. Narayan (Indian Journal of Plastic Surgery)
The severe burn injury patients (more than 40%) were studied in two randomized groups. Both groups were treated similarly except that one group received heparin both topically and systemically. Significant relief of pain, early healing in cases of superficial and deep dermal burns without hypertrophic scarring and contracture formation, early separation of eschar, excellent graft take in full thickness burns were few of the important advantages observed in heparin group patients. Significant decrease in the incidence of respiratory complications, septic shock and decreased mortality were also noticed in patients receiving heparin. The only disadvantage being that the doses required are quite heavy. No complication in the form of bleeding disorder, despite heavy dosages have been observed.